Robert Ludlum's The Treadstone transgression - Hood, Joshua (A Treadstone novel, 2022)
"A blown mission and a dead team leave Adam Hayes the last loose thread in a tapestry of betrayal in this latest high stakes international thriller from the world of Robert Ludlum"--